Leishmaniasis in Central Morocco: Seasonal Fluctuations of Phlebotomine Sand Fly in Aichoun Locality, from Sefrou Province. (8th February 2015) - Talbi, Fatima Zahra; El Ouali Lalami, Abdelhakim; Janati Idrissi, Abdellatif; Sebti, Faiza; Faraj, Chafika
Abstract : Cutaneous leishmaniases (CL) are endemic in Morocco. They are common in the human population in different localities such as Aichoun in Sefrou province, Morocco. This study was carried out in Aichoun locality from April to October 2012 in order to study the spatiotemporal trends of the main Leishmania phlebotomine vectors in this focus. Overall, 1171 sand flies, belonging to four species, were collected by sticky traps. Phlebotomus sergenti was the predominant species (78.4%) followed by Ph. perniciosus (10.5%), Ph. papatasi (7.94%), and Ph. longicuspis (3.16%). Sandflies were active during 6 months (May–October). Ph. sergenti, Ph. perniciosus, and Ph. papatasi displayed a bimodal distribution with a first peak in July and a second peak in September, while Ph. longicuspis showed a monophasic trend with a peak in August. The high abundance and the lengthy period of activity of Ph. sergenti and Ph. perniciosus, vectors of L. tropica and L. infantum, respectively, are a cause for concern as they indicate the high potential risk of Leishmania transmission in the studied areas.